2016
DOI: 10.5194/isprsarchives-xli-b1-781-2016
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Assessment Using Unmanned Aerial Vehicle (Uav) Photogrammetry

Abstract: KEY WORDS: Unmanned Arial Vehicle Photogrammetry, Remote sensing, 3D point clouds and surface models, Wetland delineation and classification, Wetland health assessment ABSTRACT:The use of Unmanned Arial Vehicle (UAV) photogrammetry is a valuable tool to enhance our understanding of wetlands. Accurate planning derived from this technological advancement allows for more effective management and conservation of wetland areas. This paper presents results of a study that aimed at investigating the use of UAV photog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…3 (ZY-3) satellite. In future research, it is suggested to use UAV Low Altitude Surveying to acquire data of higher spatial resolution for the sake of greater accuracy [80,81].…”
Section: Methodological Limits and Future Researchmentioning
confidence: 99%
“…3 (ZY-3) satellite. In future research, it is suggested to use UAV Low Altitude Surveying to acquire data of higher spatial resolution for the sake of greater accuracy [80,81].…”
Section: Methodological Limits and Future Researchmentioning
confidence: 99%
“…Remote sensing (RS) is the major source of spatial information related to the earth's surface, offering a wide range of sensors and platforms to monitor land cover and its spatial distribution. Recently, Unmanned Aircraft Systems (UASs) are widely employed in numerous RS applications including natural resource management [1][2][3]. In comparison with traditional RS, UAS technology stands out for its low-cost operation and ability to acquire image data with high spatial and temporal resolution in a flexible fashion at local scales.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, wetland characteristics are mapped with remote sensing based mainly on multispectral data from a variety of platforms, such as unmanned aerial vehicles (UAVs) (e.g., [76][77][78][79]), or satellite passive sensors, such as the Landsat Thematic Mapper (TM) and Indian Remote Sensing Satellite (IRS) [80], Satellite pour l'Observation de la Terre (SPOT) [81], WorldView-2 [82] and Sentinel-2 [83]). Figure 7 indicates that there are only a few broadband spectral regions correlating with the parameters under study, and specifically the reflectance of the shade leaves with α at the shorter wavelengths.…”
Section: Discussionmentioning
confidence: 99%